The deterrent effect of an anti-minaret vote on foreigners' location choices - Michaela Slotwinski; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2019)
In a national ballot in 2009, Swiss citizens surprisingly approved an amendment to the Swiss constitution to ban the further construction of minarets. The ballot outcome manifested reservations and anti-immigrant attitudes in regions of Switzerland which had previously been hidden. We exploit this fact as a natural experiment to identify the causal effect of negative attitudes towards immigrants on foreigners' location choices and thus indirectly on their utility. Based on a regression discontinuity design with unknown discontinuity points and administrative data on the population of foreigners, we find that the probability of their moving to a municipality which unexpectedly expressed stronger reservations decreases initially by about 40 percent. The effect is accompanied by a drop of housing prices in these municipalities and levels off over a period of about 5 months. Moreover, foreigners in high-skill occupations react relatively more strongly highlighting a tension when countries try to attract well-educated professionals from abroad.
Keywords: D83; J61; R23; Z13; 330; attitudes; foreigners; location choice; popular initiative; regression discontinuity design